Nitrogen Fixation by Soil Algae of Temperate and Tropical Soils - Stewart, W. D. P; Sampaio, M. J.; Isichei, A. O.; Slvester-Bradley, R. (Plenum Press, 2014)
Blue-green algae are common components of the microbial flora of the soil in many parts of the world (7, 8, 18, 30). In the tropics most attention has been paid to their role in rice paddy soils where, free-living (26, 27) and in symbiotic association with the water-fern Azolla (3, 19, 21, 36) they contribute substantial amounts of nitrogen to the ecosystem. In this paper we present information on the occurrence, activity, and factors affecting soil algae from tropical savanna regions of Nigeria and from the Amazon region of Brazil. The findings are compared with observations made on algae from temperate soils in Scotland. These studies complement ones from tropical (e. g. 22, 26, 27, 37) and temperate (e.g. 6, 9, 12, 28) regions.